Strategi Pengembangan Desa Wisata Syariah Berbasis BUMDes di NTB menggunakan pendekatan SWOT Matrix - sani, zainus (ITB AAS INDONESIA Surakarta, 2024)
The research aims to understand further how the concept of halal tourism villages has become a new innovation in developing tourism activities in villages based on Village-Owned Enterprises (BUMDesa) in West Nusa Tenggara province. The data used in this research is primary data obtained from interviews with experts (academics) and practitioners including the Community and Village Development Service (DPMD), the Tourism Service, the UKM Cooperative Service, the Indonesian Ulema Council (MUI). And literature studies related to the problems faced in developing BUMDesa-based halal tourism villages in NTB. Several sub-elements of strategies for developing halal tourism villages in West Nusa Tenggara were obtained from literature studies and discussions. These strategies will be outlined in the form of a questionnaire using the Strength, Weakness, Opportunity, Threat (SWOT) Matrix approach following the Internal Factor Analysis (IFAS) and External Factor Analysis (EFAS) indicators. The conclusion of this research is that the development of BUMDes-based Sharia Tourism Villages in NTB offers great potential for economic growth, cultural preservation and environmental sustainability. By actively involving the community in the entire development process, prioritizing environmental sustainability, and maintaining the authenticity of local culture and identity, Sharia Tourism Villages can create a positive impact on local communities, tourists and the surrounding environment.